STUDY OF ADAPTIVE ARCHITECTURE IN THE COMPLEX OF BALAI PEMUDA SURABAYA FROM THE COLONIAL PERIOD TO THE PRESENT - Kurniawan, Irvan; Perdhana, Dika Kusuma; Ramadhan, Luthfi Wahyu; Hidayat, Anas (ADBE, 2024)
The complex of Balai Pemuda or which is now better known as the Surabaya City Hall is one of the cultural reserve buildings that to this day is still preserved its originality. The building has a rather thick historical value, designed by a Dutch architect named Westmaes in the early 20th century and is still in use today. As the age evolves, the complex of Balai Pemuda must also be able to adapt to the change in both the shape of the façade, the use of its interior and exterior spaces, as well as the use and functionality of the building itself. The aim of this study is to see how this complex of Balai Pemuda applies an adaptive architecture that follows the times and can still preserve the historical value of its buildings. Including mapping and identifying patterns of adaptive approaches from the past to the present. This research will use qualitative research methods with a descriptive approach. Data harvesting from this research will use direct field observation techniques, internet searching and also literature studies as support. The data collected later will be analyzed in a descriptive way, so that the final results of the research so the Balai Pemuda as a cultural reserve retains its historical value by implementing the principles of adaptive architecture.